Management of Academic Supervision of School Principles in Efforts to Increase Teacher Performance - Acep Badruzaman; Achmad Sanusi; Nanang Hanafiah; Supyan Sauri (Journal of Islamicate Studies, 2022)
The implementation of the academic supervision of English teachers carried out by the Principal is carried out at least once in a school year. Some things to consider include the large number of teachers who must be supervised. The smaller the number of teachers, supervision can be carried out more than once in a school year depending on the needs of the school. The solution made by the principal in overcoming obstacles in the implementation of academic supervision, the principal seeks to select a supervisory team selectively and motivate the supervisory team and teachers and collaborate with supervisors as supervisor partners.